(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Nanofluids are fluids within which particles of nanometre sizes are suspended. In terms of thermal characteristics, nanofluids have a greater heat transfer coefficient and thermal conductivity than other traditional fluids. Bimetallic core/shell Cu/Zn particles of nanometre sizes are novel invented nanoparticle materials with considerable variations in its applications. The particles of nanometre size were suspended in a base fluid for the preparation of nanofluids for different volume fractions. A coated transitory hot wire device were built and standardized and this was subsequently employed for the determination of heat conductivities of the nanofluids for bimetallic ratios, volume fraction, base fluid temperatures and base fluids thermal conductivity. The Adaptive neuro fuzzy inference system (ANFIS) model was subsequently employed for modelling the determined results generated. A random test of 20% from various nanofluids showed a deviation less than 1% between measured and modeled results. It was inferred that heat conductivities increase with increase in the particle volume concentrations, especially when the later one at value of 1, the heat conductivities ratio approach to 1.35. Nevertheless, the shape and the method of preparing the particles of nanometre size reveals anomalous enhancements in heat conductivities of bimetallic compared to monocular metallic nanofluids.